2002
DOI: 10.1103/physreve.66.046108
|View full text |Cite
|
Sign up to set email alerts
|

Failure of thermodynamics near a phase transition

Abstract: We investigate the relation between various statistical ensembles of finite systems. If ensembles differ at the level of fluctuations of the order parameter, we show that the equations of states can present major differences. A sufficient condition for this inequivalence to survive at the thermodynamical limit is worked out. If energy consists in a kinetic and a potential part, the microcanonical ensemble does not converge towards the canonical ensemble when the partial heat capacities per particle fulfill the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 16 publications
2
46
0
Order By: Relevance
“…37 The one, well-known, exception occurs in the vicinity of phase transitions, a phenomenon we shall encounter when we apply these ideas to liquids. 38 The other kind of problem we want to touch on briefly is that of a fluid of hardspheres. Potential energy landscapes approaches typically have very little to say about systems with hard-core potentials because such systems have no minima and no stationary points in the normal sense.…”
Section: The Statistical Thermodynamics Of the Potential Energy Lmentioning
confidence: 99%
“…37 The one, well-known, exception occurs in the vicinity of phase transitions, a phenomenon we shall encounter when we apply these ideas to liquids. 38 The other kind of problem we want to touch on briefly is that of a fluid of hardspheres. Potential energy landscapes approaches typically have very little to say about systems with hard-core potentials because such systems have no minima and no stationary points in the normal sense.…”
Section: The Statistical Thermodynamics Of the Potential Energy Lmentioning
confidence: 99%
“…The interphase surface entropy goes to zero as N → ∞ in these models, leading to a linear increase of the entropy in agreement with the canonical predictions. Within the approach based on the topology of the probability distribution of observables [44] it was shown that ensemble inequivalence arises from fluctuations of the order parameter [23]. Ensembles putting different constraints on the fluctuations of the order parameter lead to a different thermodynamics.…”
Section: Ensemble Inequivalence In Phase Transition Regionsmentioning
confidence: 99%
“…This can be done by calculating the energy and multiplicity of the quantum states and use the Gibbs rule to relate these energy eigenvalues to probabilities. This road has been followed in the references [16,23,30,31,32,33]. The alternative is to introduce a Markov representation for the quantum evolution (in imaginary time or equivalently in inverse temperature) of the system.…”
Section: A the Evolution Equationmentioning
confidence: 99%